DEVELOPMENT OF THE OPERATION MODEL OF THE FOREIGN WORKERS HEALTH INSURANCE FUND IN PHANG NGA PROVINCE - Boonyarak, Jirawat (Journal of MCU Nakhondhat, 2023)
The objectives of this research aims to 1) to study the situation and operations to propel the Migrant Workers Health Insurance Fund in Phang Nga Province, 2) to find problems and obstacles in the operation of the Fund, 3) to acknowledge the proposal for the development of the fund management model, 4) to develop the fund management model in Phang Nga Province and 5) to exchange knowledge fund management. Work process using a 3-phase integrated research model. Phase 1 : Studied the context of work and proposals for development by using SWOT Analysis and POSCoRB Model. Phase 2 : Development of the model by creating a questionnaire with a scale and analyzed data for content/contextual suitability in order to create a model. Phase 3 : Testing/confirming. The results of this research found that there are 3 main funds in Phang Nga Province, namely the Phang Nga Provincial Public Health Office's Fund, the Phang Nga Hospital's Fund, and the Takuapa’s Hospital Fund. Working context show that the main challenge is service quality competition between public and private hospitals. While some employers / foreign workers think that buying a health insurance card is more wasteful than paying on a per-time basis because he is still of good health and working age , if they have a little sick they able to receive treatment and pay from time to time that cheaper than buying an annual pass. Some foreign workers buy health insurance card when sick or requiring expensive medical services. The model development proposal has 2 main factors : Improving internal work processes and synthesis of external measures, including 5 sub-processes. Model test/verification results found that it was possible to actually use/beneficial to the development of the Migrant Workers Health Insurance Fund in Phang Nga Province